Interventricular Differences in Action Potential Duration Restitution Contribute to Dissimilar Ventricular Rhythms in ex vivo Perfused Hearts - Handa, Balvinder S.; Lawal, Saheed; Wright, Ian J.; Li, Xinyang; Cabello-García, Javier; Mansfield, Catherine; Chowdhury, Rasheda A.; Peters, Nicholas S.; Ng, Fu Siong (Frontiers in Cardiovascular Medicine, 2019)
Background Dissimilar ventricular rhythms refer to the occurrence of different ventricular tachyarrhythmias in the right and left ventricles or different rates of the same tachyarrhythmia in the two ventricles. Objective We investigated the inducibility of dissimilar ventricular rhythms, their underlying mechanisms, and the impact of anti-arrhythmic drugs (lidocaine and amiodarone) on their occurrence. Methods Ventricular tachyarrhythmias were induced with burst pacing in twenty-eight Langendorff-perfused Sprague Dawley rat hearts (14 control, 8 lidocaine, 6 amiodarone) and bipolar electrograms recorded from the right and left ventricles. Fourteen (6 control, 4 lidocaine, 4 amiodarone) further hearts underwent optical mapping of transmembrane voltage to study interventricular electrophysiological differences and mechanisms of dissimilar rhythms. Results In control hearts, dissimilar ventricular rhythms developed in 8/14 hearts (57%). In lidocaine treated hearts, there was a lower cycle length threshold for developing dissimilar rhythms, with 8/8 (100%) hearts developing dissimilar rhythms in comparison to 0/6 in the amiodarone group. Dissimilar ventricular tachycardia (VT) rates occurred at longer cycle lengths with lidocaine vs control (57.1±7.9 vs 36.6±8.4 ms, p<0.001). The ratio of LV:RV VT rate was greater in the lidocaine group than control (1.91± 0.30 vs 1.76±0.36, p<0.001). The gradient of the action potential duration (APD) restitution curve was shallower in the RV compared with LV (0.12 ± 0.03 vs 0.002 ± 0.03, p=0.015), leading to LV-to-RV conduction block during VT. Conclusion Interventricular differences in APD restitution properties likely contribute to the occurrence of dissimilar rhythms. Sodium channel blockade with lidocaine increases the likelihood of dissimilar ventricular rhythms.